Adaby Ijtimȃ’i Pattern In The Interpretation Of The Risâlat Al-Qaûl Al-Bayân By Sulaiman Al-Rasuli Al-Minangkabawi - Syamsuri, Syamsuri (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2024)
One of the purposes of writing interpretations is to show that the Qur'an will always be a guide and an answer to various problems that occur in people's lives. Of course, the problems faced by each interpreter are different, so this is one of the causes for the emergence of various works of interpretation with different methods and patterns. Risâlat Al-Qaûl Al-Bayân is a work by Nusantara scholars from Minangkabau written in Minangkabau-Malay Arabic script and first published in 1929 AD by Mathba'at al-Islâmiyah. This study employs a literature review with descriptive and qualitative explanations. The results show that the interpretation of Risalat al-Qaul al-Bayan has an adabi ijtima'i pattern. As evidenced in several detentions against verses of the Koran, the pressure on social aspects of al-Rasuli When folding QS. Al-Fajr verses 17-20, QS. Al-Balad 14-16, QS. Al-Dhuha 9-10, and QS. Al-Ma'un al-Rasuli, for example, the public is encouraged to care more for the mustad'afîn (weak people), such as the poor and orphans. Because al-Rasuli saw that people's lives at that time were beginning to be influenced by a lifepattern of hedonism and prioritizing themselves, while there were still many poor people and abandoned orphans.